The Effect of Complementary Therapy With Facial and Lavender Aromatherapy on Anxiety Management Among Postpartum Mothers - NATHASIA HARYONO (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
The postpartum period is a critical phase in a woman's reproductive life, characterized by physical and psychological vulnerability due to hormonal changes, the postpartum recovery process, and adaptation to the new role as a mother. This condition often triggers postpartum anxiety, which, if not properly managed, can affect the mother's mental health and the quality of childcare. Complementary interventions such as facial acupressure (totok wajah) and lavender aromatherapy have been widely recommended due to their relaxation mechanisms that help reduce emotional tension. This study aimed to determine the effect of facial acupressure and lavender aromatherapy on reducing anxiety levels among postpartum mothers at Grandmed Hospital Lubuk Pakam. The research design used was a pre-experimental study with a one-group pretest–posttest approach involving 28 postpartum mothers selected through a total sampling technique. Anxiety levels were measured before and after the intervention using a questionnaire instrument. Data analysis was conducted using the Shapiro–Wilk test and the Wilcoxon test because the data were not normally distributed (p < 0.05).The results showed that before the intervention, respondents were categorized as having mild anxiety (35.7%), moderate anxiety (42.9%), and severe anxiety (21.4%). After the intervention, 35.7% of respondents no longer experienced anxiety, 42.9% were categorized as having mild anxiety, and 21.4% had moderate anxiety, while severe anxiety was no longer found. The Wilcoxon test showed a p-value of 0.000, indicating a significant difference between anxiety levels before and after the intervention.Physiologically, facial acupressure promotes relaxation through stimulation of acupressure points, while lavender aromatherapy, which contains linalool and linalyl acetate, works by reducing sympathetic nervous system activity. Therefore, the combination of these two interventions is proven to be effective as a non-pharmacological method for reducing anxiety in postpartum mothers.